Dynamics of Phonatory Posturing at Phonation Onset - Shiba, Travis L. (Laryngoscope, 2015)
INTRODUCTION: In speech and singing, the intrinsic laryngeal muscles set the pre-phonatory posture prior to the onset of phonation. The timing and shape of the pre-phonatory glottal posture can directly affect the resulting phonation type. We investigated the dynamics of human laryngeal phonatory posturing. METHODS: Onset of vocal fold adduction to phonation was observed in 27 normal subjects using high-speed video recording. Subjects were asked to utter a variety of phonation types (modal, breathy, pressed, /i/ following sniff). Digital videokymography (DVK) with concurrent acoustic signal was analyzed to assess the timing of the following: onset of adduction to final phonatory posture (FPT), phonation onset time (POT), and phonatory posture time (PPT). Final phonatory posture time was determined as the moment at which the laryngeal configuration used in phonation was first achieved. RESULTS: 33 audio-visual recordings met inclusion criteria. Average FPT, PPT, and POT were as follows: 303, 106, and 409 ms for modal; 430, 104, and 534 ms for breathy; 483, 213, and 696 ms for pressed; and 278, 98 and 376 ms for sniff-/i/. The following posturing features were observed: (1) Pressed phonation: increased speed of closure just prior to final posture, complete glottal closure, and increased supraglottic hyperactivity (SGH), and (2) Breathy phonation: decreased speed of closure prior to final posture, increased posterior glottal gap (PGG), and increased mid-membranous gap (MMG). CONCLUSIONS: Phonation onset latency was shortest for modal, and longest for pressed voice. These findings are likely explained by glottal resistance and subglottal pressure requirements.